Colangiopancreatografia por ressonância magnética associada à ressonância magnética convencional na estenose biliar: revisão sistemática de acurácia em teste diagnóstico - Cavalcanti Neto, Augusto Jose [UNIFESP] (2016)
Objective: To evaluate the accuracy of the association Cholangiopancreatography Magnetic Resonance associated with MRI of the Upper Abdomen in the detection, location and determining the nature of the stricture of bile ducts, by systematic review and meta-analysis of studies test diagnosis. Methods: A review of the methodology Cochrane was adopted, using Review Manager 5 software (version 5.3.1). Search were done in MEDLINE, EMBASE, LILACS, CENTRAL (Cochrane Central Register of Controlled Trials), The Cochrane Library, The Cochrane Hepato-Biliary Group Controlled Trials Register e The Cochrane Hepato-Biliary Diagnostic Test of Accuracy Studies Register.databases. Inclusion and exclusion criteria were adopted for the participants of the sample, index test and reference standard. The assessment of methodological quality of the selected articles was performed using the QUADAS 2. Statistical analysis was performed using SAS software, version 9.2. Results: The search in the databases resulted in a final sample of 14 studies. Meta-analysis was not performed for the location of the stenosis. For stenosis detection 12 studies were included and in determining the nature of the stricture 9 studies were included in the sample of the meta-analysis. The studies were considered in methodological quality with high risk of bias. S sensitivity analysis was not performed. The sensitivity and specificity for detection of stenosis index test was 98% (95% - (93% -99%) and 97% (95% - 93% -98%) and in determining the nature was 96% (95% - 89% -99%) and 84% (95% - 72% -92%), respectively. Conclusions: The combination of Magnetic Resonance Cholangiopancreatography with MRI of the Abdomen in this study with heterogeneity proved to be an accurate tool for the detection and determination of nature of the stricture of bile ducts.